Prevalencia de tumores venéreos caninos transmisibles en perros domésticos (Canis lupus familiaris) atendidos en el mes de noviembre 2018 en el Santuario Canino de Gustavo , sector la Resbalosa, San Lorenzo, Manta. - Chiang Crosby, Pamela Nicole (2019)
The objective of the present work is a study of the prevalence of canine transmissible venereal tumors in domestic dogs (Canis lupus familiaris). This study was made in november 2018, in Santuario Canino de Gustavo, sector la Resbalosa, San Lorenzo, Manta, where 85 dogs destined to be neutered were examined; the samples were examined in a microscope and as a result there were 3 positive cases. The study was made with a cuantitive and cualitive focus, considering as variables the age, sex, breed, anatomic condition of the animal and the location of the tumor, as in the positive cases there was more frequency of the neoplásica in whole female half blood adult dogs. There was a prevalence of 4 % of affected dogs to this pathology. As a recommendation of this work, it is indicated to evaluate a bigger number of animals, or to make relations between different areas to determine where does a bigger prevalence of TVT exists.